Efektivitas Penggunaan Alat Pelindung Diri (APD) di Laboratorium Kesehatan Primer di Indonesia Literature Review - Muhammad Iqbal; Asmawati Achamad; Radhiah Zakaria; Intan Sari (Yayasan Literasi Sains Indonesia, 2025)
The use of Personal Protective Equipment (PPE) in primary health laboratories is a crucial step in mitigating the risks of exposure to biological, chemical, and physical hazards that may endanger laboratory personnel. This study aims to evaluate the effectiveness of PPE in reducing occupational risks and to identify factors influencing the compliance levels of laboratory staff with safety standards. The methodology employed is a systematic literature review, analyzing various scientific articles, research reports, and credible sources from 2019 to 2024. The findings indicate that compliance levels with PPE usage remain variable, influenced by several factors, including the availability of PPE, understanding of the importance of occupational safety, and user comfort. Several challenges encountered include discomfort during use, a lack of awareness among laboratory personnel, and resource limitations in primary health facilities such as community health centers. Therefore, there is a need to strengthen occupational safety policies through the provision of ergonomic PPE, enhancement of education and training for laboratory personnel, and stricter supervision of safety protocol implementation. By taking these measures, the effectiveness of PPE usage can be improved, thereby creating a safer work environment and supporting the health of laboratory personnel.